EFFECTIVENESS OF TRAINING STUDENTS ON INTER CULTURAL COMMUNICATION FOR GLOBAL FITMENT AT WORKPLACE-A PILOT STUDY!!! - Shrivastava, Shruti; Prasad, Vineeta (International Journal of Psychosocial Rehabilitation, 2020)
Inter Cultural Communication is an emerging area of research. With the fast pacing technological advancement and sporadic business across the world-there is a lot of mingling between people from different culture. The business world has taken a new shape and form in which cross cultural teams working with each other has highly increased. The way of doing business globally is transitioning, and there is a need for the new workforce entering global markets for employment to be trained on the same. The skill set required to do business in today’s world is different and is ever changing. The new workforce therefore needs to be trained on these emerging skill sets so that they can not only gain employment but also sustain it. This paper discusses the importance of training the emerging workforce (professional students) on importance of inter cultural communication, and have productive conversations with the diverse customers and stakeholders from across culture in their employment. In order to highlight the effectiveness of training students while they are in their education years-the researcher worked with a sample of 100 final year engineering and MBA students of a technical university based out of Delhi-NCR. These students were trained on improving upon their inter cultural communication with Japanese customers for future employments- by using different activities as a part of an intervention process. The intervention process used training material, activities and video based learning related to effective inter cultural communication with Japanese customers. A pre-and posttest method was used for a group of 100 students, and their improvement scores were measured. The findings of the study highlight a marked improvement in the post-test scores of the groups which indicates effectiveness of the training intervention used. This paper recommends imparting focused training to professional students studying in engineering and MBA schools on intercultural communication strategies to aid in improving communicating with stakeholders across culture thereby enhancing their workplace communication.